Analysis of Roadside Land Use Changes and Landscape Ecological Risk Assessment Based on GF-1: A Case Study of the Linghua Expressway - Mengdi Wen; Liangliang Zhang; Huawei Wan; Peirong Shi; Longhui Lu; Zixin Zhao; Zhiru Zhang; Jinhui Wu (Remote Sensing)
The rapid construction of expressways in China has brought significant economic and social benefits, but it has also imposed substantial ecological pressures, particularly in sensitive regions. Landscape ecological risk assessment, as an important means to predict and measure the adverse effects of human activities on the ecological environment, is being paid more and more attention. However, most studies focus on the static landscape mosaic pattern and lack dynamic analysis. Moreover, they mainly focus on the ecological effect of the road operation stage, ignoring the monitoring and analysis of the whole construction process. Based on this, the current study examines the landscape ecological risk and land use changes along the Linghua Expressway in Gansu Province using high-resolution GF-1 remote sensing imagery. A landscape ecological risk assessment (LERA) model was employed to quantify the land use changes and assess the ecological risks before and after the expressway construction between 2018 and 2022. The results revealed a decrease in cropland and forest land, accompanied by an increase in the grassland and road areas. The landscape ecological risk index decreased from 0.318 in 2018 to 0.174 in 2022, indicating an improvement in ecological resilience. However, high-risk zones remain near the expressway, emphasizing the need for continuous monitoring and proactive ecological management strategies. These findings contribute to sustainable infrastructure planning, particularly in ecologically sensitive regions.